Answer :

4x – 2x = 6 - 3

2x = 3


x = .


L.H.S: 4() + 3 = 9


R.H.S: = 6 + 2() = 9


Since L.H.S. = R.H.S


Hence, the solution is correct.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve each of theRD Sharma - Mathematics